Knowledge, attitudes, and practices toward linezolid–serotonergic drug interactions: a cross-sectional study - Aldairem, Atheer; Almohareb, Sumaya N.; Alowais, Shuroug A.; Shawaqfeh, Mohammad S.; Alzahrani, Abdullah A.; Alzahrani, Abdullah Y.; Alqahtani, Khalid H.; Bin Saleh, Khalid (Frontiers in Pharmacology, 2025)
BackgroundConcomitant use of linezolid with serotonergic agents may lead to serotonin syndrome, a rare but serious complication. This study assessed healthcare providers’ knowledge, attitudes, and practices (KAP) to identify gaps and inform strategies to enhance patient safety.MethodsWe conducted a nationwide, cross-sectional survey among physicians, pharmacists, and nurses practicing in Saudi Arabia. Participants completed a validated questionnaire designed to assess KAP related to linezolid–serotonergic drug interactions. KAP scores were categorized and analyzed using logistic regression to identify predictors associated with higher performance.ResultsAmong 116 respondents, 69.0% reported awareness of linezolid–serotonergic drug interaction. However, only 30.2% achieved high knowledge scores (≥6.7/10). Correct identification of serotonin syndrome, Hunter diagnostic criteria, and the recommended 2-week washout period was limited (34.5%, 34.5%, and 41.4%, respectively). Pharmacists had the highest knowledge scores (mean 5.52), followed by physicians (5.18) and nurses (2.79). In multivariable analysis, prior awareness of the interaction (AOR, 23.52; 95% CI, 2.90–190.72) and international training (AOR, 3.51; 95% CI, 1.07–11.53) were associated with higher knowledge scores. Both knowledge and attitude were significantly associated with safer practice behaviors (OR 3.04 and 8.75, respectively; p < 0.05).ConclusionPersistent gaps in knowledge and safe prescribing practices related to the linezolid–serotonergic interaction were identified among healthcare providers in Saudi Arabia, reflecting a broader challenge globally. These findings support the need for targeted educational interventions and institution-level policies to improve awareness, enhance patient safety, and reduce preventable harm.